Fiscal policy from Reagan to Blair : the left veers right - Roy, Ravi K., 1969-; Denzau, Arthur (Routledge frontiers of political economy, 2004)
"Whether fiscal policy conversion is seen as a good or bad occurrence, this book shall unite both left and right to better explain the process. Students and academics of international political economy, public policy and politics will find this book a good addition to their reading lists."--Jacket.